Persebaran Tumbuhan Obat Sipaet dan Dadap Serep di Kabupaten Tapanuli Utara Menggunakan Model MaxEnt - Handika Ananda Pudan Simamora; Martina Restuati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Indonesia has great potential in the utilization of traditional medicinal plants, including Sipaet (Tithonia diversifolia) and Dadap Serep (Erythrina subumbrans) which have been used for generations by the people of North Tapanuli Regency. However, data information related to the spatial distribution and ecological existence of these two species is not yet systematically available. This descriptive-exploratory study with a spatial quantitative approach aims to map the spatial distribution, predict the potential existence of Sipaet (Tithonia diversifolia) and Dadap Serep (Erythrina subumbrans) medicinal plants in North Tapanuli Regency. The analysis uses the Maximum Entropy (MaxEnt) model version 3.4.4. The model accuracy is validated using the Area Under the Curve (AUC) value. Based on the results of the Species Distribution Modeling (SDM) analysis using MaxEnt, it shows that Tithonia diversifolia has a high habitat suitability (0.7-0.9), and its distribution is most dominantly influenced by seasonal rainfall and solar radiation, with a model accuracy level classified as good (AUC = 0.812). Meanwhile, Erythrina subumbrans showed moderate to low habitat suitability (0.4-0.6), influenced by average monthly temperature and solar radiation, but with low to moderate model accuracy (AUC = 0.612).